Assessment of knowledge and skills of hand hygiene among representatives of three generations of the family living in different regions of Uzbekistan (Eurasian Medical Research Periodical, 2022)
With the help of an interview survey, the knowledge and skills in hand hygiene issues of urban and rural populations of various regions of the republic were assessed, taking into account the subjective opinion of three generations living in the same family. The results of the study showed that the provision of favorable conditions for hand hygiene is noted in 40.1% of the studied households of the urban population and in 30.7% of the studied households of the rural population. The study of the level of knowledge and skills on hand hygiene in the context of family generations showed that the vast majority of respondents showed a good level of knowledge (90% or more). However, in matters of actual hand hygiene in all three generations, there was a difference of 24.2%. The largest number of respondents believe that lectures and conversations of medical workers (73.4–86.3%), television (66.7–90.7%), as well as conversations with family members (70.8-88.5%) were the most significant sources of information for improving knowledge and skills in hand hygiene. The responses of parents and children were supplemented by two more parameters – the Internet (47.1-73.2%) and books, magazines, brochures (33.1–68.6%)